Ethical evaluation of the diagnosis of diseases causing disability in prenatal life - Moya, Graciela (Acta Bioethica, 2014)
The goal of prenatal diagnosis causes a controversial dilemma. Some authors sustain that it favors better development and adaptation of the child to be born and family, since, by defining the moral statute of the fetus as inherent, he/she must receive the same moral considerations that the child already born. Others consider that avoiding the birth of children with these pathologies is a preventive measure to diminish the prevalence of genetic diseases. Thus, the child to be born is not considered a person and the disability is interpreted as damage for the child and his/her family, which must be avoided. There is tension to determine whether prenatal diagnosis is a medical practice to the service of human beings with the goal to limit damage and human suffering, or rather an eugenic liberal practice. Three concepts are involved in this conflict: the person, disability and prevention of diseases. The goal of this article is to reflect about the interpretation of these concepts in different bioethical views, in order to reach a better understanding of them and applying technological advances while respecting human condition.